Suitability mapping for integrated aquatic food production systems – Decision Support System User Guide. Burmese version - Smith, Bethany; Teoh, Shwu Jiau; Leemans, Kimio; Aung, Mo; Khaing, Kyaw Win; Mon Soe, May Hsu; Win Maung, KuMuDara; Akester, Michael; Dubois, Mark (WorldFish, 2022)
The Integrated Aquatic Food Production System Decision Support System (IAFP DSS) provides a standardised approach to suitability analysis, enabling decision makers and stakeholders to engage with the technique in a simplistic yet comprehensive manner. The tool is suitable for application by a range of bodies including governmental and non-governmental organisations, research organisations and NGOs that have an interest in supporting the development of tailored and targeted investments for integrated aquatic food production systems within a given region. This report is the user guidelines translated in Burmese which support the training of the trainers implemented in Myanmar.